2010
DOI: 10.22358/jafs/66268/2010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breed and dietary level of avocado fat on the N and energy balance in young pigs

Abstract: The effect of breed and dietary avocado level on the total apparent digestibility (RAD) and balance of nitrogen (N) energy, in young pigs, was studied. Four Pelón Mexicano (PM) and four Yorkshire × Landrace (Y×L) barrow male pigs (39.2 kg average inital liveweight) distributed in two groups according to a change over design in a 2×2 factorial arrangement (breed and diet) were used. The pigs received on a pair feeding basis (0.10 kg DM/kg W 0.75 per day), the experimental diets. The diets were formulated to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
1
13
0
5
Order By: Relevance
“…ab Diferentes literales superindicados por fila indican diferencias entre dietas con p < valor. (Grageola et al, 2010), y es una fruta que puedes modular la calidad de la carne, de acuerdo Percentages of protein, ash and moisture were similar in all three diets. There was a significant increase (p < 0.01 a p < 0.001) in γ-tocopherol, TPC and antioxidant DPPH and ABTS activity in the Longissimus dorsi muscle including AM in the diets (Table 3); with a lineal effect in these variables (p < 0.01 a p < 0.001), for which the content increases with a higher AM inclusion (Table 4).…”
Section: Resultados De La Valoración Nutricional Del Músculo Longissimentioning
confidence: 79%
See 2 more Smart Citations
“…ab Diferentes literales superindicados por fila indican diferencias entre dietas con p < valor. (Grageola et al, 2010), y es una fruta que puedes modular la calidad de la carne, de acuerdo Percentages of protein, ash and moisture were similar in all three diets. There was a significant increase (p < 0.01 a p < 0.001) in γ-tocopherol, TPC and antioxidant DPPH and ABTS activity in the Longissimus dorsi muscle including AM in the diets (Table 3); with a lineal effect in these variables (p < 0.01 a p < 0.001), for which the content increases with a higher AM inclusion (Table 4).…”
Section: Resultados De La Valoración Nutricional Del Músculo Longissimentioning
confidence: 79%
“…Avocado (Persea americana Mill) is a fruit that gathers important nutritional characteristics, with the contribution of liposoluble vitamins (vitamin E) that serve as antioxidants, phenolic compounds, lacks cholesterol, with a low percentage of saturated fatty acids, and in contrast a high content of unsaturated fatty acids (Méndez-Zúñiga et al, 2019). Furthermore, in avocadoformulated diets, the rectal digestibility of nutrients is relatively high (Grageola et al, 2010;Hernández-López et al, 2016 a ;Franquez et al, 2017 AM0, AM5 y AM10 que corresponden al 0 (control), 5 y 10 % de la materia seca (Tabla 1).…”
Section: Materials Y Métodosmentioning
confidence: 99%
See 1 more Smart Citation
“…however, due to lack of adherence to certain commercial standards and industrial processes, the seeds and skin are discarded. Avocados are rich in unsaturated fatty acids, tocopherols, and other important phytochemical compounds that are responsible for initiating positive biological responses in animals, including pigs [34]. According to Grageola et al [34], dietary avocado is responsible for maintaining the equilibrium between nitrogen and energy balance in young pigs.…”
Section: Nutritious Dietary Resources Derived From Malus Domestica Wamentioning
confidence: 99%
“…Avocados are rich in unsaturated fatty acids, tocopherols, and other important phytochemical compounds that are responsible for initiating positive biological responses in animals, including pigs [34]. According to Grageola et al [34], dietary avocado is responsible for maintaining the equilibrium between nitrogen and energy balance in young pigs. Furthermore, Wood et al [35] reported that the juiciness and flavour of avocados are considered as sensory traits that can influence the composition of meat, the intramuscular fat (IMF), and fatty acid composition.…”
Section: Nutritious Dietary Resources Derived From Malus Domestica Wamentioning
confidence: 99%